The Mediating Role of Health Perception in the Effect of Trust in Physicians on Treatment Compliance: The Case of Sakarya Province - Özişli, Ömer; Kara, Enes; Er, Kadri (The European Research Journal, 2026)
Objective: Trust is a key element of healthcare services, as individuals prefer to receive treatment from physicians they trust in both knowledge and practice. Based on this, the study examines the mediating role of health perceptions in the effect of trust in physicians on treatment adherence. Methods: The research was conducted in Sakarya Province between 25 October and 30 December 2024, using face-to-face and online surveys. The population included residents aged 18 and over, and the required sample size was 384 at a 95% confidence level. Using convenience sampling, data were obtained from 471 individuals. Results: The results show that trust in physicians increases treatment compliance while decreasing health perception, with health perception partially mediating this relationship. Treatment compliance depends on trust levels and individuals’ health evaluations. The positive relationship between trust in physicians and treatment adherence (r = 0.527) and its negative relationship with health perception (r = −0.442) confirm both directional effects. This pattern demonstrates the multidimensional nature of patient behaviour. Therefore, effective health communication and strong physician–patient interaction are critical for improving treatment compliance. Conclusion: Trust in physicians and health perception are key determinants of treatment compliance. The mediating role of health perception indicates its strong effect on transforming trust in physicians into treatment adherence. The study highlights the importance of strengthening trust in physicians and improving individuals' health perceptions through effective communication strategies to enhance treatment compliance.